Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire à domicile - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2024)

Pratique # 17 : Les séances de dialogue au Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (2021)

Pratique # 26 : Accès santé jeunesse Péninsule acadienne (ASJPA) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)
fs-ref-orig: van Kemenade, S., Benoît, J., Savard, S. et Savard, J. (2025). Pratique # 26 : Accès santé jeunesse Péninsule acadienne (ASJPA). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_pratiques_ novatrices.html fs-code-orig: van Kemenade-2025c

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire à domicile (infographie) - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (2024)

Pratique # 25 : Accès éQUITÉ : Simplifier l’accès aux services de santé en français (Société Santé en français) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)

Pratique # 19 : Les outils de rappel du Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (2021)
fs-ref-orig: Benoit, J., Dagnogo, D.S., Savard, J., & Savard, S. (2021, mise à jour 2025). Pratique # 19 : Les outils de rappel du Réseau de santé Horizon (Nouveau-Brunswick). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/ repertoire_pratiques_novatrices.html. fs-code-orig: Benoit-2025c

Pratique # 27 : Accueil centralisé (Centre francophone du Grand Toronto, Ontario) - van Kemenade, Solange; Benoît, Josée; Savard, Sébastien; Savard, Jacinthe (2025)
fs-ref-orig: van Kemenade, S., Benoît, J., Savard, S. et Savard, J. (2025). Pratique # 27 : Accueil centralisé (Centre francophone du Grand Toronto, Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_ pratiques_novatrices.html. fs-code-orig: van Kemenade-2025d

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire en maison de retraite (infographie) - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (2024)

Pratique # 18 : Le plan de contingence du Réseau de santé Horizon (Nouveau-Brunswick) - Benoît, Josée; Dagnogo, Djenaba Sarah; Savard, Jacinthe; Savard, Sébastien (2021)
fs-ref-orig: Benoît, J., Dagnogo, D.S., Savard, J. & Savard, S. (2021, mise à jour 2025). Pratique # 18 : Le plan de contingence du Réseau de santé Horizon (Nouveau-Brunswick). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops. ca/repertoire_pratiques_novatrices.html fs-code-orig: Benoit-2025b

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire en maison de retraite - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2024)

A self-assessment tool for healthcare and social service provision in French: What use for managers? - Savard, Sébastien; Savard, Jacinthe; van Kemenade, Solange; Benoît, Josée; Tabor, Michelle (Healthcare Management Forum, 2020)
Language is an important determinant of health, and lack of access to quality, linguistically adapted healthcare and social services negatively impacts users. Besides the lack of bilingual resources, our previous research on Francophone minority community seniors’ trajectories through these services shed light on important and nonobvious challenges currently faced by organizations offering healthcare and social services to this population. Current service provision appeared limited due to organizations working in silos with suboptimally used resources for integrating active offer of French language services throughout the continuum of care. This situation led our team to create the Organizational and Community Resources Self-Assessment Tool for Active Offer and Continuity of French Language Healthcare and Social Services, which is intended to help managers and service providers promote and facilitate the integration of active offer throughout the continuum of service provision. This article describes the Tool’s creation, content validation, and pilot-testing.

Structural facilitators and barriers to access to and continuity of French-language healthcare and social services in Ontario’s Champlain region - Savard, Jacinthe; Bigney, Kte; Kubina, Lucy-Ann; Savard, Sébastien; Drolet, Marie (Healthcare Policy, 2020)
Purpose: The purpose of this article is to examine access to and continuity of French-language healthcare and social services in Ontario's Champlain region through an analytical framework that incorporates people seeking care, their caregivers and the linguistic component of care into a health and social service system bounded by community, organizational, political and symbolic structures. Methods: Experiences of French-speaking seniors seeking care and those of health and social service providers and managers from two qualitative exploratory studies are used to describe trajectories through the system. Results: Participants exposed how, together with community vitality, issues within each of the system's symbolic, political or regulatory and organizational structures influence these trajectories. Conclusions: To meet the needs of francophone seniors, additional work is needed to increase French-language services coordination within the organizational, regulatory and policy structures of the health and social service system.

Management strategies to improve French language service coordination and continuity for official language Francophone seniors in Canada - de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette; Kubina, Lucy-Ann (Healthcare Management Forum, 2020)
Evidence suggests that language barriers present obstacles to healthcare access and quality for Francophone seniors in official language minority communities across Canada. Addressing language barriers and providing continuity is challenging, as French language services (FLSs) rely heavily on bilingual providers and the practice of active offer by all staff. This qualitative research used semi-structured group and individual interviews to explore mechanisms supporting FLS coordination and continuity in two Canadian provinces. Identification of the language variable in health records, virtual healthcare, and FLS directories are conducive to FLS continuity, but financial and resource limitations present major obstacles. Management strategies to facilitate continuity of FLS across health organizations are discussed.

L’accès aux services en français, de la connaissance des défis à l’accompagnement des organisations vers le changement. - Savard, Sébastien; Savard, Jacinthe; Sauvé-Schenk, Katrine; van Kemenade, Solange; Benoît, Josée (Minorités linguistiques et société, 2024)
Depuis 2011, le Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (GReFoPS) cherche à mieux comprendre les facilitateurs et les obstacles à l’offre de services en français dans un contexte linguistique minoritaire au Canada. Dans cet article, les auteurs présentent un bilan de près de 12 ans de recherche sur le sujet, en décrivant les facteurs individuels et organisationnels qui influencent l’offre de services en français. Les résultats de ces études ont mis en lumière quelques mécanismes organisationnels ou interorganisationnels qui ont permis l’émergence de pratiques novatrices pour améliorer l’offre de services en français dans les services communautaires et institutionnels. On y décrit également des outils créés pour aider les gestionnaires de ces services à identifier des mesures et des mécanismes pouvant répondre aux besoins des usagers francophones en situation minoritaire. Mots-clés : accès, services sociaux et de santé, francophones, contexte minoritaire, Canada

Strategies to improve French language health and social service continuity for seniors in Ontario and Manitoba - Savard, Jacinthe; Savard, Sébastien; de Moissac, Danielle; Giasson, Florette; Kubina, Lucy-Ann (Linguistic Minorities and Society, 2021)
Access to health and social services in one’s official language of choice is an important component of quality and safety of care for seniors. Access can be fragmented, even in the context of legislation guaranteeing the right to receive such services, and in areas with a higher proportion of bilingual providers. Using a community-based participatory approach, we identified mechanisms promoting or impeding the clinical integration of health and social French language services intended for seniors living in two Canadian Francophone minority communities. Thirteen recommendations highlight the possibility for new initiatives to promote a continuum of French language health and social services in a minority context, involving collaboration among a variety of actors at all levels of our analytical framework: service trajectory (providers); francophone communities; organizational; political and regulatory; and symbolic (values) structures. Keywords: seniors, linguistic minorities, service integration, health and social services, continuity of care

Apprentissage de l’offre active des services sociaux et de santé en français par module de simulation interprofessionnelle au bénéfice des francophones en situation minoritaire au Canada - Giroux, Isabelle; Savard, Jacinthe; Tyerman, Jane; Savard, Sébastien; Benoît, Josée; Kengneson, Cris-Carelle (Revista de Llengua i Dret, 2025)
Résumé La formation des futurs prestataires de soins à l’offre active (OA) des services sociaux et de santé (SSS) en français est essentielle pour permettre l’accès équitable à des services de qualité pour les francophones en situation minoritaire (FSM) au Canada. L’apprentissage par module de simulation interprofessionnelle est une avenue prometteuse à évaluer. L’objectif du présent travail est d’évaluer la satisfaction et l’efficacité perçue de l’apprentissage de l’OA des SSS en français à l’aide d’un module de simulation interprofessionnelle spécifique, le MODULE-IP-SIM-OA. En ce qui concerne la méthodologie, des stagiaires de programmes en SSS de l’Université d’Ottawa ont complété le dit module, suivi d’un débreffage synchrone et d’un questionnaire de rétroaction en ligne, entre mai et décembre 2023. Les 216 stagiaires issus de neuf disciplines ont rapporté des taux élevés de satisfaction et d’efficacité perçue concernant le MODULE-IP-SIM-OA et son débreffage. Cet apprentissage, jugé efficace par les stagiaires, pourrait avoir des retombées positives sur l’offre de services aux FSM afin d’atténuer les barrières linguistiques en santé. Resum La formació dels futurs professionals de la salut sobre l’oferta activa (OA) dels serveis socials i de salut (SSS) en francès és essencial per permetre un accés equitatiu a serveis de qualitat a les persones francòfones en situació minoritària (FSM) al Canadà. L’aprenentatge mitjançant un mòdul de simulació interprofessional és una via prometedora que cal explorar. L’objectiu d’aquest treball és avaluar el nivell de satisfacció i d’eficàcia percebuda de l’aprenentatge de l’OA dels SSS en francès amb l’ajuda d’un mòdul de simulació interprofessional específic, el MODULE-IP-SIM-OA. Pel que fa a la metodologia, diversos estudiants en pràctiques de programes de SSS de la Universitat d’Ottawa van completar aquest mòdul, seguit d’una sessió de debrífing síncrona i d’un qüestionari de valoració en línia, entre els mesos de maig i desembre de 2023. Els 216 estudiants, provinents de nou disciplines diferents, van aportar respostes que indiquen nivells alts de satisfacció i d’eficàcia percebuda en relació amb el MODULE-IP-SIM-OA i el debrífing posterior. Aquest aprenentatge, que els participants van considerar eficaç, podria tenir efectes positius en l’oferta de serveis als FSM per reduir les barreres lingüístiques en l’àmbit de la salut. Abstract Training future care providers in the active offer (AO) of social and health services (SHS) in French is essential for ensuring equitable access to quality services for Francophones in minority contexts (FMS) in Canada. Learning through an interprofessional simulation module is a promising approach that warrants evaluation. The purpose of this paper is to assess the satisfaction and perceived effectiveness of learning the AO of SHS in French using a specific interprofessional simulation module, the MODULE-IP-SIM-OA. Regarding methodology, between May and December 2023, trainees from SHS programs at the University of Ottawa completed this module, followed by a synchronous debriefing and an online feedback questionnaire. The 216 trainees from nine disciplines reported high levels of satisfaction and perceived effectiveness regarding the MODULE-IP-SIM-OA and its debriefing. This learning experience, considered effective by the trainees, could have positive impacts on service delivery to FMS and help reduce language barriers in healthcare. Resumen La formación de los futuros profesionales de la salud sobre la oferta activa (OA) de los servicios sociales y de salud (SSS) en francés es esencial para permitir un acceso equitativo a servicios de calidad a las personas francófonas en situación minoritaria (FSM) en Canadá. El aprendizaje mediante un módulo de simulación interprofesional es una vía prometedora que hay que explorar. El objetivo de este trabajo es evaluar el nivel de satisfacción y de eficacia percibida del aprendizaje de la OA de los SSS en francés con la ayuda de un módulo de simulación interprofesional específico, el MODULE-IP-SIM-OA. Con respecto a la metodología, varios estudiantes en prácticas de programas de SSS de la Universidad de Ottawa completaron este módulo, seguido de una sesión de debriefing síncrona y de un cuestionario de valoración en línea, entre los meses de mayo y diciembre de 2023. Los 216 estudiantes, provenientes de nueve disciplinas diferentes, aportaron respuestas que indican niveles altos de satisfacción y de eficacia percibida en relación con el MODULE-IP-SIM-OA y el debriefing posterior. Este aprendizaje, que los participantes consideraron eficaz, podría tener efectos positivos en la oferta de servicios a los FSM para reducir las barreras lingüísticas en el ámbito de la salud.

Pratiques novatrices en santé mentale pour les populations de langue officielle minoritaire à Terre-Neuve-et-Labrador et dans les Territoires du Nord-Ouest - van Kemenade, Solange; Bouchard, Louise; Savard, Jacinthe; Savard, Sébastien; Oukouomi, G.; Michel, J. N. (Université d'Ottawa, Chaire de recherche de l’Université d’Ottawa et de l’Institut du Savoir Montfort sur la santé des francophones de l’Ontario et Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2021)

Vers de nouvelles approches en santé mentale : possibilités et limites pour les francophones en situation minoritaire à Terre-Neuve-et-Labrador et aux Territoires du Nord-Ouest - Savard, Sébastien; van Kemenade, Solange; Bouchard, Louise; Savard, Jacinthe; Oukouami D, Ghisleine; Michel, Jean Nephetaly (Canadian Social Work Review / Revue canadienne de service social, 2024)
De nouvelles approches axées sur la cybersanté mentale l’aide à la navigation du système, les cliniques sans rendez-vous, ainsi que les approches plus traditionnelles comme les lignes d’aide et de crise cohabitent afin de promouvoir ou d’intervenir précocement en santé mentale. Comment ces interventions répondent-elles aux besoins des francophones en contexte linguistique minoritaire alors que la communication est au coeur d’une consultation réussie? Objectif : Documenter six initiatives à Terre-Neuve-et-Labrador et dans les Territoires du Nord-Ouest. Méthode : Études de cas, incluant trente-six entrevues semi-dirigées auprès des autorités sanitaires, des fournisseurs de soins et des usagers. Résultats : La gratuité, l’anonymat, la rapidité, la présence des pairs travailleurs, l’absence de jugement et des démarches simples facilitent l’accès aux programmes. Parmi les limites, l’insuffisance de services en français et l’accent sur les thérapies brèves peuvent affecter la continuité des services, notamment pour les usagers francophones. Conclusion : Malgré les efforts pour améliorer l’offre de services en santé mentale aux francophones, des lacunes subsistent. L’article présente certaines stratégies qui permettraient d’améliorer l’offre de ces services. Mots-clés : Santé mentale, cybersanté mentale, initiatives novatrices, Terre-Neuve-et-Labrador, Territoires du Nord-Ouest, soins par paliers, francophones en situation minoritaire

Active offer of services in Canada’s official languages: development of a patient experience questionnaire - Sauvé-Schenk, Katrine; Pignac, Sarah; Kemenade, Solange Van; Savard, Sébastien; Prud'homme, Denis; Savard, Jacinthe (Journal of Communication in Healthcare, 2026)
ABSTRACT Background: In the bilingual Canadian context, the use of a preferred official language with healthcare providers is linked to optimized communication, respectful patient-centered care, improved safety and quality of services. This study aimed to develop and test a questionnaire that measures patients’ experience of how language was considered during an outpatient health encounter. Methods: French and English questions were drafted based on a literature review. Questionnaire content and flow were validated through focus groups with experts and service users. Question understanding and clarity was verified with cognitive interviews and pre-tests with diverse service users. The final questionnaire was pilot tested in three health organizations and temporal stability, and construct validity was verified. Results: Participants were nine anglophone and eleven francophone experts and service users for the focus groups, six anglophone and six francophone service users for the cognitive interviews, eleven anglophone and ten francophone service users for the pre-test. The resulting questionnaire has 31 experience-related questions organized under six themes: arrival/greeting, interpretation and translation services, language of health services, relationship with healthcare providers, visibility of official languages and follow-up. The questionnaire is completed online in French or English. The questionnaire was pilot tested with 199 participants in three sites. Temporal stability was moderate to good. Initial evidence of construct validity was demonstrated, suggesting that the questionnaire is adequate to evaluate patient experience. Conclusion: This questionnaire is the first known bilingual patient-experience tool, focused on the active offer of services in official languages during outpatient healthcare encounters, with preliminary validation.

Pratique # 12 : Les Lunchs-causeries au Centre de services communautaires Vanier (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2021, mise à jour 2025). Pratique # 12 : Les Lunchs-causeries au Centre de services communautaires Vanier (Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_pratiques_novatrices.html fs-code-orig: Savard-2025g

Pratique # 10 : Les points de service satellites (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2021). Pratique # 10 : Les points de service satellites (Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/ repertoire_pratiques_novatrices.html fs-code-orig: Savard-2021d

Pratique # 11 : The Information and Support Guide for Caregivers (Québec) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2021). Pratique # 11 : The Information and Support Guide for Caregivers (Québec). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https:// www.grefops.ca/repertoire_pratiques_novatrices.html fs-code-orig: Savard-2021e

Practice # 3: The Pavillon Omer Deslauriers: A Francophone Unit at Bendale Acres (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., & Kubina, L.A. (2021, updated 2025). Practice # 3: The Pavillon Omer Deslauriers: A Francophone Unit at Bendale Acres (Ontario). In: GReFoPS. Directory of Innovative Practices in Health and Social Services in Official Language Minority Contexts. https://www.grefops.ca/directory_innovative_practices.html fs-code-orig: Savard-2025b

Pratique # 13 : Une infirmière de Santé publique dans un centre de services communautaires qui assure l’aiguillage des aînés (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)
fs-ref-orig: Savard, J., Savard, S., van Kemenade, S., Benoît, J., Buhay, C., Youbi, S., et Kubina, L.A. (2021, mise à jour 2025). Pratique # 13 : Une infirmière de Santé publique dans un centre de services communautaires qui assure l’aiguillage des aînés (Ontario). Dans : GReFoPS. Répertoire de pratiques novatrices en santé et service social en langue officielle en contexte minoritaire. https://www.grefops.ca/repertoire_ pratiques_novatrices.html fs-code-orig: Savard-2025h

Pratique # 14 : Les Foires d’information de la Fédération des aînés et des retraités francophones de l’Ontario (FARFO) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 6 : Café de Paris (Nouveau-Brunswick) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Implementation of Innovative Strategies to Increase French Language Services in Three Canadian Health and Social Services Organizations. Research report, - Savard, Sébastien; Savard, Jacinthe; Benoît, Josée; Sauvé-Schenk, Katrine; de Moissac, Danielle; Durand, François; Dupuis-Blanchard, Suzanne (2024)
fs-ref-orig: Savard, S., Savard, J., Benoît, J., Sauvé-Schenk, K., de Moissac, D., Durand, F., Dupuis-Blanchard, S. (2024). Implementation of Innovative Strategies to Increase French Language Services in Three Canadian Health and Social Services Organizations. Research report, Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (GReFoPS), Université d'Ottawa. fs-code-orig: Savard-2024d

Évaluation de la mise en œuvre de services en français en contexte minoritaire : développement d’un questionnaire sur l’expérience des usagers - Sauvé-Schenk, K; Savard, Jacinthe; Savard, Sébastien; Prud’homme, Denis; van Kemenade, Solange; Le Callonnec, L; Pignac, S (2022)

Prolonged Impact of the COVID-19 Pandemic on the Well-being and Roles of Family/Friend Caregivers of Older Adults Living at Home in Canadian Official Language Minority or Majority Communities - Savard, Jacinthe; Savard, Sébastien; Duong, Patrick; Hatungimana, Nelly Oriane; Benoit, Josée; De Moissac, Danielle; Dupuis-Blanchard, Suzanne; Robitaille, Annie (Canadian Journal on Aging / La Revue canadienne du vieillissement, 2026)
Résumé Contexte. Des études menées pendant la pandémie de COVID-19 soulignent que le confinement a réduit l’accès aux services et accru les responsabilités et l’isolement des proches aidants. Objectif. Cette étude examine les répercussions à long terme chez 83 proches aidants de personnes âgées provenant de quatre provinces canadiennes. Méthodes. Les participants ont rempli un questionnaire en ligne entre octobre 2021 et février 2022, puis à nouveau six mois plus tard, sur l’aide fournie, le soutien reçu, la langue des services et le bien-être psychologique. De plus, huit aidants ont participé à une entrevue qualitative. Résultats. La plupart des services d’aide à domicile ont été maintenus pendant la pandémie, certains avec un personnel réduit, à l’exception des services de répit et de transport. Les aidants ont accru leur aide pendant les confinements, et cette implication accrue s’est poursuivie en 2022. Ils ont perçu un impact négatif de la pandémie sur leur santé et celle de la personne aidée. Les participants issus de communautés linguistiques minoritaires officielles ont décrit des difficultés supplémentaires pour accéder aux services dans leur langue préférée. Discussion. Une meilleure reconnaissance des besoins des aidants contribuera à soutenir leur rôle en tant que partenaires au sein des organismes de santé. Abstract Background. Studies conducted during the COVID-19 pandemic highlighted that confinement reduced access to services and increased caregivers’ responsibilities and isolation. Objectives. This study examines the longer-term impacts among 83 unpaid caregivers of older adults from four Canadian provinces. Methods. Participants completed an online questionnaire between October 2021 and February 2022, and again 6 months later, on the assistance provided, support received, language of services, and psychological well-being. Additionally, eight caregivers participated in a qualitative interview. Findings. Most home support services were maintained during the pandemic – some with restricted staffing – except for respite and transportation services. Caregivers increased their assistance during the lockdowns, and this higher involvement persisted in 2022. They perceived a negative impact of the pandemic on their health and that of the care recipient. Participants from official language minority communities described additional challenges accessing services in their preferred language. Discussion. Greater recognition of caregivers’ needs will help support their role as partners within health organizations.